Causes of Low Academic Performance in Adamu Augie College of Education, Argungu Kebbi State - Danmaigoro, Aliyu; Usman Fakai, Rufai; Ibrahim , Umar (MultiTech Publisher, 2024)
Abstract The study was to find out the causes of low academic performance of students in Adamu Augie College of Education, Argungu in Kebbi State. The population of the study consisted of 400 students of Adamu Augie College of Education, Argungu out of which 120 were randomly selected. A structural questionnaire was used for data collection. The data collected from the respondents were analyzed using frequency counts and mean scores for all the research questions. The findings revealed that all variable factors are responsible for the low academic performance of students except the involvement of parents in the Parents Teachers Association (P.T.A). Based on these findings, the following recommendations are made: Teachers should employ various teaching strategies as well and the teaching must be from simple to complex for a better understanding of their students, Teachers should develop positive attitudes towards the students under his/her control to ensure effective learning and better performance of their students and Parents should give more attention and proper monitoring to their children education.